ANTIMICROBIAL ACTIVITIES AND THE FIRST ISOLATION OF 4-NITROBENZOIC ACID TETRAHYDROFURAN-2-YL-METHYLESTER AND 4-HYDROXY-5-METHYLFURAN-3-ONE FROM TERRESTRIAL STREPTOMYCES SP. - SAYED A. AHMED; MAHMOUD AL-REFAI; ALZAHRAA OSAMA; EMADELDIN M. KAMEL (International Journal of Pharma and Bio Sciences, 2016)
In our investigation of the crude extracts from the terrestrial derived Streptomycete isolate sp. Wo 990, two compounds namely, 4-nitrobenzoic acid tetrahydrofuran-2-yl-methylester (1) and 4-hydroxy-5- methylfuran-3-one (5) were obtained for the first time from microorganisms. In addition, 2- phenylacetamide, 5-methyl-1H-pyrimidine-2,4-dione, 2-amino-3-phenyl-propionic acid and 2-(6-aminopurin-9-yl)-5-methyl-sulfanylmethyl-tetrahydrofuran-4-diol were isolated. The structures of the new compounds 1 and 5 were elucidated on the basis of spectroscopic analysis (1D and 2D), mass spectra and comparison with the literature data.